THU0626 SOCIAL NETWORKS AS A SOURCE OF INFORMATION FOR PATIENTS WITH RHEUMATIC DISEASES. (June 2019) - Fernández-Ávila, Daniel G.; Barahona-Correa, Julián; Romero-Alvernia, Diana; García, Angel; Muñoz, Oscar
Abstract : Background: Internet is an informative source for patients with different diseases. False information in social networks about health issues is a growing problem. Rheumatology is no stranger to this problem and there is a lot of false information regarding rheumatic diseases. Objectives: To show objective data on misinformation published in social networks available to spanish-speaking rheumatic patients Methods: We create accounts on Facebook (FB) and Google unique for this work. Multimedia was included in Spanish, with a convenience sampling according to the deployment of the platform (FB) or in descending order for reproductions on YouTube (YT). Two independent reviewers extracted information on online time, number of reproductions and characteristics of the most popular videos. Videos consulted on 10-11-18. Results: With the search term "rheumatoid arthritis" (RA), the most reproduced video is titled "celery green juice for arthritis" (6.4 million reproductions). Of the first 50 videos with more reproductions, 39 are of natural or home remedies such as vinegar, "moringa", etc., and 35 videos indicate in their content, that they can cure RA. With the term "lupus", the most reproduced video is titled "God's tea, cure chronic tiredness, thyroid, arthritis, lupus and vertigo" (1.4 million reproductions). Of the first 50 videos with more reproductions, 31 correspond to natural or home remedies such as celery, thyme, diets among others and 29 videos indicate that they can cure lupus. With the term "fibromyalgia", the most reproduced video is entitled "I am 61 years old and this cured my arthritis, vertigo, fibromyalgia, lupus, chronic fatigue and the thyroid" (1.1 million reproductions). Of the 50 first videos with more reproductions, 40 are of natural or home remedies such as thyme, tea, among others and 33 videos indicate that they can cure the disease. With the data of the videos uploaded online in October 2018, 50 videos were chosen in YT and FB. There was no correlation between online time and the number of views on any platform. In FB, 56% of the videos contained false information, with no difference in online time in both groups (16 [12-22] vs 18 [13-25], p = 0.3).). In YT, only 38% was considered false information, without differences between groups in online time (19 [11-26] vs 22 [12-24]). Conclusion: YT and FB are social networks with a high content of false information. The majority of available videos promise to cure different rheumatic diseases (even several simultaneously). This is the first work of a line of research that seeks to highlight the high degree of misinformation. We will continue to analyze other diseases and social networks, to make publications and communications in different media and to alert local regulatory entities. Disclosure of Interests: None declared